Effect of Infant Health Problem, Mother's Depression and Marital Relationship on Infant Abuse in Korea: Mediating Pathway of Marital Relationship - Kyoung-Eun Kim, PhD; Jung-Hyun Choi, RN, PhD; Young Hee Kim, RN, PhD (Elsevier, 2014)
Purpose: The purpose of this study is to test a model linking infant health problem, mother's depression and marital relationship to infant abuse. Methods: This study employed a cross-sectional survey design. Data were collected from 2009 Data of Index Studies for Korean Children and Adolescents Development. Survey data from 1,060 infants and their mothers (including infant health status and infant physical illness scale, depression scale, marital relationship scale, and child abuse scale) were used to test the model. The model was tested using path analysis techniques within structural equation modeling. Results: The model fit indices suggested that the original hypothesized model adequately fit the data (χ2 = .33, df = 5, p = .84, Tucker-Lewis Index = 1.04, Comparative Fit Index = 1.00, Root Mean Square Error of Approximation = .00). Infant health problem and mother's depression had a negative direct effect on marital relationship, which in turn had a direct negative effect on infant abuse. Infant health problems directly affected infant abuse and also influenced infant abuse indirectly through the marital relationship. Mother's depression had significant direct effects on infant abuse and also influenced infant abuse indirectly through the marital relationship. Conclusion: The findings from this study demonstrate the fundamental importance of infant health as linked to the mother's mental health, and marital relationship and increasing the quality of marital relationship may be the key to infant abuse prevention.